Factors affecting variance in Classroom Assessment Scoring System scores: season, context, and classroom composition. Issue 11 (2nd November 2017) - Buell, Martha; Han, Myae; Vukelich, Carol
ABSTRACT: Early care and education programme quality is usually assessed at the classroom level. One such measure of classroom quality is the classroom assessment scoring system (CLASS). In an effort to ensure higher quality programming, the CLASS is being used to direct teacher professional development. However, there has been relatively little research on environmental features that lead to differences in CLASS scores. As the CLASS becomes a regulatory tool, more research is needed on factors that can affect CLASS scores. In this quasi-experimental, descriptive study, we compare CLASS scores over the course of three years. Our data indicate patterns of seasonal fluctuation with rising scores fall to spring, but the scores revert to lower levels in the subsequent fall. We also found a relationship between CLASS scores and the proportion of boys in a classroom. These findings call for additional exploration of the factors that influence preschool CLASS scores.